The role of cognitive capital in supply chain resilience: a focus on resilient interorganizational culture in supply chain networks - Daghar, Anis (Cranfield University, 2024)
This thesis's central thread comprises three papers (i.e., Papers 1, 2, and 3). Paper 1 is a literature review consolidating the state of research on collaborative interorganizational relationships in supply chain risks. Paper 2 is a case study that explores the role of cognitive capital in supply chain resilience. Finally, Paper 3 is a case study analyzing how resilient interorganizational culture functions in multi-tier supply networks. Firms increasingly engage in developing collaborative interorganizational relationships (CIRs) to manage supply chain risks (SCRs) and improve supply chain resilience (SCRES). While there is a wealth of fragmented studies on CIRs and SCRs, the literature still lacks a synthetic theoretical articulation of how various aspects of CIRs affect different SCRs. Employing a systematic literature review approach, Paper 1 grounds CIRs in the social capital theory to explain the role of structural, relational, and cognitive capital residing in these relationships in various SCRs. The review reveals that the three social capital dimensions positively and negatively affect different SCRs (i.e., environmental, supply, manufacturing, demand, information, financial, transportation). The findings suggest that the perceived SCRs can influence structural and relational capital. Providing a future research agenda, the literature review calls for researching how the underexplored cognitive capital aspect influences SCRES. Recognized as the most challenging dimension to operationally separate from other social capital dimensions, cognitive capital has remained an elusive concept. Adopting a buyer-supplier case study approach during a global disruption, Paper 2 unveils different cognitive capital elements (e.g., shared goals, assumptions, values, kinesics language, multilingualism, virtual negotiation, prior disruption experience, shared process capabilities), and explains how they enable positively and episodically the four SCRES temporal capabilities to prepare, respond, recover, and learn, under contingencies of increased and decreased demands, and suppliers’ geographical proximity. Forming the core identity of interorganizational relationships, interorganizational culture is a fundamental element of cognitive capital representing symbols and meanings shared by groups or individuals from different organizations through intersections of cultures and boundaries. Multiple research calls have highlighted the lack of research on interorganizational culture in SCRES. Going beyond the established dyadic view, Paper 3 enriches the existing literature by exploring the role of interorganizational culture in SCRES in a multi-tier supply chain network. Using a case study of a disrupted multi-tier supply chain network, Paper 3 identifies and explains how aligned and misaligned interorganizational cultural elements (i.e., shared goals, expectations, understanding, processes, values) impact the SCRES elements of collaboration, flexibility, visibility, and velocity. Applying balance theory, the study characterizes a resilient network-level interorganizational culture by highlighting different supply chain network-level mechanisms (i.e., cultural alignment, propagation, transitivity) influencing SCRES elements differently.
Keywords: Collaboration; buyer-supplier relationships; interorganizational relationships; interorganizational culture; supply network; supply chain risks; supply chain resilience; social capital; cognitive capital; balance theory